Analysis of the Character in the Movie Series Moon Knight by Marvel Cinematic Universe in 2022 - Nurfatah, Ali Murti; Passandaran, Yosi Maeleona; Muniroh, Zumrotul (JEdu: Journal of English Education, 2024)
The purpose of this study is to explain the character of the main character in MCU's Moon Knight film series in 2022 and the types of main character based on the literary analysis approach. The method used in this research is descriptive qualitative. The research uses Florence Littauer Theory. The result of this study is that the main character gets the type of character type in theory, Sanguinis amounted to twenty-one data of sanguinis character type with a percentage of 31.34%, eighteen data of choleric character type with a percentage of 26.86%, fourteen data of melancholy character type with a percentage of 20.89%, fourteen data of phlegmatic character type with a percentage of 20.89%. The overall analysis of the character Marc Spector and his 2 Alteregos has a dominant character, namely the sanguinis type. It can be seen as in the charismatic nature, being able to lead and inspire others, also found in the nature of openness and curiosity, having the nature of socialization and optimism, the ability to adapt to different situations and interact with others in a friendly and pleasant way, having the nature of self-confidence and assertiveness, and the last character trait that is full of energy.